4g+9=2(g-6)+2y

Simple and best practice solution for 4g+9=2(g-6)+2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g+9=2(g-6)+2y equation:


Simplifying
4g + 9 = 2(g + -6) + 2y

Reorder the terms:
9 + 4g = 2(g + -6) + 2y

Reorder the terms:
9 + 4g = 2(-6 + g) + 2y
9 + 4g = (-6 * 2 + g * 2) + 2y
9 + 4g = (-12 + 2g) + 2y

Solving
9 + 4g = -12 + 2g + 2y

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-2g' to each side of the equation.
9 + 4g + -2g = -12 + 2g + -2g + 2y

Combine like terms: 4g + -2g = 2g
9 + 2g = -12 + 2g + -2g + 2y

Combine like terms: 2g + -2g = 0
9 + 2g = -12 + 0 + 2y
9 + 2g = -12 + 2y

Add '-9' to each side of the equation.
9 + -9 + 2g = -12 + -9 + 2y

Combine like terms: 9 + -9 = 0
0 + 2g = -12 + -9 + 2y
2g = -12 + -9 + 2y

Combine like terms: -12 + -9 = -21
2g = -21 + 2y

Divide each side by '2'.
g = -10.5 + y

Simplifying
g = -10.5 + y

See similar equations:

| (8x^2+x)-(x^2+3x)= | | 2(2c+11d)+8c-14d+-3cd= | | 6(c+7)-14=25 | | 3y-7=5[2y-3]+4 | | 7x+3=42 | | 3x+42= | | -12+-7k=30 | | 23=4x+5y | | -100+4s=100 | | -100+4s=-50 | | t+3t-7=4+-7 | | 70x+40=6 | | -100+4s=50 | | 4/2x-5/2x+9/2x | | 10-5+3x+2x=0 | | 5x-28=3x+10 | | (2x^2+4x)+(3x^2+2x)= | | 4/2x | | 1+2+3=24 | | 2+4w=-26 | | (8x+5)+(19-8x)= | | 67x+13=6 | | 7+2+8=216 | | -5+9d=49 | | -17+3x=-41 | | 8/3*10 | | g^3+3g^2-y-3=0 | | 0=2+2Q+2Q^2 | | 2y=1.5x-8 | | 4v^5(v^2-4v+14)= | | 11-9m=70 | | (7/6n-84n+288)-5/5n^2-40n |

Equations solver categories